1969
DOI: 10.1071/sr9690333
|View full text |Cite
|
Sign up to set email alerts
|

The penetration of clays by fine probes and root tips

Abstract: Penetration tests were conducted in a saturated clay using fine probes and pea radicles. The point resistance encountered by fine probes, Qp, was related inversely to the rate of penetration of the probe. The resistance increased exponentially with decreasing voids ratio, ew,; at any given value of ew more resistance was offered by clay that had been remoulded than by finely aggregated clay. When radicles grown through a bed of soil crumbs encountered cores of moderately consolidated saturated clay, they merel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 1 publication
0
21
0
2
Order By: Relevance
“…This was in close agreement with a number of studies using reconstructed soils (Taylor and Gardner 1963;Taylor etal. 1966;Camp and Lund 1968;Cockroft et al 1969). Other authors (Grimes et al19'15;Gerard et al 1982; Ehlers et al 1983;Yapa et al 1988;Vepraskas and Wagger 1989) have reported higher values.…”
Section: Root Penetrationmentioning
confidence: 72%
“…This was in close agreement with a number of studies using reconstructed soils (Taylor and Gardner 1963;Taylor etal. 1966;Camp and Lund 1968;Cockroft et al 1969). Other authors (Grimes et al19'15;Gerard et al 1982; Ehlers et al 1983;Yapa et al 1988;Vepraskas and Wagger 1989) have reported higher values.…”
Section: Root Penetrationmentioning
confidence: 72%
“…5) shows a relatively uniform distribution of points around the 1:1 line although the model may be underpredicting SMR slightly at observed SMRN6000 kPa. However, the RMSE values were still relatively large when one considers that the rate of root growth may approach zero at a SMR of 2000-3000 kPa (Taylor et al, 1966;Cockroft et al, 1969). Becher (1998) has found large variability in SMR between aggregates extracted from the same soil.…”
Section: Undisturbed Soilsmentioning
confidence: 96%
“…A pulverização dos horizontes superficiais, em decorrência do cultivo contínuo e sob condições de chuva, propicia a eluviação da argila dispersa, levando à conseqüente obstrução dos poros (Helalia et al, 1988;Fuller et al, 1995). Podem também ocorrer penetrações de argila através de finos canais secundários formados pelo avanço do crescimento de raízes de plantas com sistema radicular fasciculado (Cockroft et al, 1969), como é o caso da cana-de-açúcar no presente trabalho. 2.…”
Section: Figura 10 Macroagregados Parcialmente Destruídos No Horizonunclassified